2020
DOI: 10.1093/molbev/msaa186
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryote-Conserved Methylarginine Is Absent in Diplomonads and Functionally Compensated inGiardia

Abstract: Methylation is a common post-translational modification of arginine and lysine in eukaryotic proteins. Methylproteomes are best characterised for higher eukaryotes, where they are functionally expanded and evolved complex regulation. However, this is not the case for protist species evolved from the earliest eukaryotic lineages. Here, we integrated bioinformatic, proteomic and drug-screening datasets to comprehensively explore the methylproteome of Giardia duodenalis - a deeply-branching parasitic protist. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 108 publications
(134 reference statements)
0
11
0
Order By: Relevance
“…This research also demonstrated that TbMOB1A interacts with the T. brucei NDR kinase TbPK50, a protein with high homology to the T. gondii NDR kinases. More recently, MOB proteins were also detected and are conserved in other kinetoplastids, i.e., Trypanosoma rangeli, Trypanosoma cruzi, and Leishmania major [160,161] and in the fornicatan Giardia [162][163][164]. Conserved Mob1 genes have also been identified in Trichomonas vaginalis and Entamoeba histolytica, protozoans belonging to the phyla Parabasalia and Amoebozoa, respectively [165,166].…”
Section: Non-alveolate Protozoamentioning
confidence: 97%
“…This research also demonstrated that TbMOB1A interacts with the T. brucei NDR kinase TbPK50, a protein with high homology to the T. gondii NDR kinases. More recently, MOB proteins were also detected and are conserved in other kinetoplastids, i.e., Trypanosoma rangeli, Trypanosoma cruzi, and Leishmania major [160,161] and in the fornicatan Giardia [162][163][164]. Conserved Mob1 genes have also been identified in Trichomonas vaginalis and Entamoeba histolytica, protozoans belonging to the phyla Parabasalia and Amoebozoa, respectively [165,166].…”
Section: Non-alveolate Protozoamentioning
confidence: 97%
“…Protein arginine and lysine residues are commonly methylated in eukaryotic cells. 27 Arginine methylation is an influential PTM that occurs on nonhistone and histone proteins, affecting their interactions, such as protein‐protein and protein–nucleic acid interactions. 28 In mammals, nine enzymes, PRMTs 1‐9, promote arginine methylation.…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis of amino acids patterns surrounding methylation sites reveal different residues in K-Me and R-Me. The vicinity of lysine methylated sites are enriched for glutamic acids (E/Glu), something also seen in P. falciparum [21] and Giardia duodenalis [22] and arginine methylated sites are enriched upstream for arginine (R/Arg) and downstream for methionine (M/Met). Well-defined patterns of amino acids, such “RGG”, are not always surrounding targets of PRMTs [57] and, likewise, are not always defined for PKMT [58].…”
Section: Discussionmentioning
confidence: 99%
“…In Plasmodium falciparum , arginine [21] and lysine [22] methylated proteins are involved in diverse biological pathways, for example, RNA metabolism, protein synthesis, transport, proteolysis, protein folding and chromatin organization. In the deep-branching Giardia duodenalis [23], interestingly, methyl-arginines (and arginine-methyltransferases) are absent, but their biological functions appear to be compensated by methyl-lysines, which are regulated between its different life-cycle stages. For the TriTryps, global studies about protein methylation are only available for Leishmania and T. brucei .…”
Section: Introductionmentioning
confidence: 99%